Role of mucin 2 gene for growth in Anas platyrhynchos: a novel report - Kumar Murmu, Anuj; Pal, Aruna; Debnath, Manti; Chakraborty, Argha; Pal, Subhamoy; Banerjee, Samiddha; Pal, Abantika; Ghosh, Nilotpal; Karmakar, Utpal; Samanta, Rajarshi (Frontiers in Veterinary Science, 2023)
Introduction The mucin gene is expressed in the mucous membrane of the inner layer of the internal organs. Intestinalmucin 2 (MUC2), amajor gel-formingmucin, represents a primary barrier component of mucus layers. Materials and methods This is the first report on the role of mucin genes in growth traits in animals. In this study, we randomly studied Bengal ducks (Anas platyrhynchos) reared from day old to 10 weeks of age under an organized farm and studied the growth parameters as well as body weight and average daily body weight gain. Result and discussion We characterized the mucin gene for Bengal ducks and observed glycosylation and EGF1 (EGF-like domain signature) as important domains for growth traits in ducks. We observed a better expression profile for the mucin gene in high-growing ducks in comparison to that of low-growing ducks with real-time PCR. Hence, the mucin gene may be employed as a marker for growth traits.